2017
DOI: 10.1002/glia.23281
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific deletions of the glutamate transporter GLT1 differentially affect seizure activity and neurodegeneration in mice

Abstract: Glial glutamate transporter GLT1 plays a key role in the maintenance of extracellular glutamate homeostasis. Recent human genetic studies have suggested that de novo mutations in GLT1 (EAAT2) cause early-onset epilepsy with multiple seizure types. Consistent with these findings, global GLT1 null mice show lethal spontaneous seizures. The consequences of GLT1 dysfunction vary between different brain regions, suggesting that the role of GLT1 dysfunction in epilepsy may also vary with brain regions. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Consistent with our data, a reduction in astroglial glutamate transporter expression associated with increased extracellular glutamate levels has been found in the sclerotic hippocampus of patients with temporal lobe epilepsy (Cavus et al, , ; Jabs, Seifert, & Steinhäuser, ; Mathern et al, ; Proper et al, ) as well as in a tuberous sclerosis epilepsy model (Wong et al, ). Furthermore, knockout mice for the glial glutamate transporter GLT‐1 develop spontaneous seizures and hippocampal pathology resembling those observed in temporal lobe epilepsy patients with hippocampal sclerosis (Petr et al, ; Sugimoto et al, ; Tanaka et al, ). In addition, pharmacological block of GLT‐1 decrease the threshold to trigger epileptiform activity and increase the occurrence of spontaneous epileptiform discharges in the rat cortex (Campbell & Hablitz, , ).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our data, a reduction in astroglial glutamate transporter expression associated with increased extracellular glutamate levels has been found in the sclerotic hippocampus of patients with temporal lobe epilepsy (Cavus et al, , ; Jabs, Seifert, & Steinhäuser, ; Mathern et al, ; Proper et al, ) as well as in a tuberous sclerosis epilepsy model (Wong et al, ). Furthermore, knockout mice for the glial glutamate transporter GLT‐1 develop spontaneous seizures and hippocampal pathology resembling those observed in temporal lobe epilepsy patients with hippocampal sclerosis (Petr et al, ; Sugimoto et al, ; Tanaka et al, ). In addition, pharmacological block of GLT‐1 decrease the threshold to trigger epileptiform activity and increase the occurrence of spontaneous epileptiform discharges in the rat cortex (Campbell & Hablitz, , ).…”
Section: Discussionmentioning
confidence: 97%
“…Petr et al (2015) reported that only astrocytic but not neuronal deletion of GLT1 induced seizure activity, suggesting that the function of an astrocytic membrane protein is particularly important in the pathophysiology of multiple behaviors related to glutamatergic system. Furthermore, brain-region-specific deletion of GLT1 in the diencephalon, brainstem, and spinal cord could result in excess mortality and lethal spontaneous seizure (Sugimoto et al, 2018). Likewise, GLT1 dysfunction in the dorsal forebrain is involved in the pathogenesis of infantile epilepsy (Sugimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, astrocytic-, but not neuronal-specific deletion of GLT1 induced fatal epilepsy, suggesting that astrocytic GLT1 performs critical functions (Petr et al, 2015). Further, recent data indicated that selective deletion of GLT1 in the diencephalon, brainstem and spinal cord was sufficient to reproduce the phenotypes (excess mortality, decreased body weight, and lethal spontaneous seizure) (Sugimoto et al, 2018). Deletion of GLT1 in habenula astrocytes increased neuronal excitability and depression-like behaviors (Cui et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SLC1A2 has been known to be a GLU transporter, which transports GLU outside the synapse into the cell to balance GLU levels . SCL1A2 is reported to have lower expression in patients with epilepsy . In this study, we investigated its role by upregulating its expression in TLE rats.…”
Section: Discussionmentioning
confidence: 98%